The Impact of Covid-19 on the Income of Fishermen Processing Anchovy (Stolephorus sp) in Hajoran Village, Pandan Subdistrict, Central Tapanuli Regency, North Sumatra Province - Herpina Pasaribu; Trisla Warningsih; Darwis AN (Faculty of Fisheries and Marine, Universitas Riau, 2023)
The Covid-19 pandemic in Indonesia occurred in March 2019. The implementation of the PSBB and social/physical distancing has disrupted the economy, one of which is the fisheries sector. The impact caused by the reduced income of fishermen's families is that of anchovy processing fishermen in Hajoran Village. This research was conducted from 21 June to 30 June 2022 in the Hajoran Village. The purpose of this study was to analyze the impact of Covid-19 on anchovy income and marketing before and after the Covid-19 pandemic in Hajoran. The method used is survey method. Anchovy fishermen consist of 46 people. The research data were obtained through direct observation and documentary interviews. Based on the results of the analysis, it is known that both before and after the Covid-19 pandemic had an impact on the income of fishers processing anchovies, where the average income of fishermen before the pandemic was IDR 238.913 and after. during the pandemic the average income of fishermen is IDR 1.213.043. In addition, the Covid-19 pandemic also had an impact on the marketing of anchovies, namely during the pandemic the price of anchovies was IDR 60.000/Kg while during the Covid-19 pandemic it was IDR 30.000/Kg.